1986
DOI: 10.1159/000457075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroid Status on Lung and Heart Beta-Adrenergic Receptors in Fetal and Newborn Sheep

Abstract: The effect of altered thyroid status on the development of beta-adrenergic receptor (BAR) density and affinity was investigated in ovine fetal and newborn heart and lung. Fetal (119-121 days gestation) and newborn (2-3 days of age) sheep underwent either thyroidectomy alone, thyroidectomy plus infusion of a large dose of T3 or sham operation. Eight days later BAR were measured in heart and lung using the tritiated radioligand dihydroalprenolol. There was no apparent effect of altered thyroid status on fetal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

1989
1989
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 19 publications
0
13
2
Order By: Relevance
“…Interestingly, there is a low level of TR occupancy in rats until the second postnatal week (46). Whereas the ␤1AR is expressed and coupled to important physiologic responses, thyroid hormone alone or in combination with corticosteroids does not increase ␤1AR receptor expression or density during fetal or early postnatal development (17,33,34). This is in contrast to studies in older animals and humans where thyroid hormones have clearly been shown to increase ␤1AR expression (28).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, there is a low level of TR occupancy in rats until the second postnatal week (46). Whereas the ␤1AR is expressed and coupled to important physiologic responses, thyroid hormone alone or in combination with corticosteroids does not increase ␤1AR receptor expression or density during fetal or early postnatal development (17,33,34). This is in contrast to studies in older animals and humans where thyroid hormones have clearly been shown to increase ␤1AR expression (28).…”
Section: Discussionmentioning
confidence: 88%
“…Studies from our group and others have shown that the ␤1AR is expressed during late fetal development in both rodents and sheep and coupled to important physiologic responses (11)(12)(13)(14)(15)(16)(17)(18). Interestingly, thyroid hormone alone or in combination with corticosteroids does not further increase ␤1AR receptor expression or density during fetal or early postnatal development (17,18,33,34). This is in marked contrast to the studies in older animals and humans where thyroid hormones have clearly been shown to increase ␤1AR expression and the increase has been shown to be at the level of gene transcription (28).…”
mentioning
confidence: 88%
“…These responses may therefore be enhanced by b 3 -adrenergic agonist treatment, at least 24 h after birth. Failure to observe any additional effect of b 3 -adrenergic agonist on the postfeeding rise in colonic temperature before 12 h is likely to be linked to the rapid increase in sympathetic stimulation associated with parturition (Eliot et al 1981) and the concomitant rise in b-receptor abundance (Padbury et al 1986). …”
Section: Figurementioning
confidence: 99%
“…Methimazole-treated CR lambs did not exhibit an age-related decline in heart rate despite heat production (per kilogram body weight) decreasing with age. These differences may be linked to changes in the ontogeny of cardiac ,J-adrenergic receptors, for which T3 is necessary to maintain a high binding capacity (Padbury, Klein, Polk, Lam, Hobel & Fisher, 1986). In addition, metabolic demands on the heart are much greater in CR lambs and this additional work could have a direct effect on hypertrophy of cardiac muscle (Cotterell & Dauncey, 1991) as well as the distribution of cardiac output (Weiss & Tse, 1995).…”
Section: Thyroid Hormones and Thermoregulationmentioning
confidence: 99%